The Effect of Carbon Emissions on Earnings Quality with The Moderation of Gender Diversity in Indonesia - Annisa, Rara; Atmini, Sari; Noval Adib (Universitas Muhammadiyah Surakarta, 2025)
This study analyzes the impact of carbon emissions on earnings quality, examining how gender diversity on corporate boards moderate this relationship. Using panel data regression with Moderated Regression Analysis (MRA), the study investigates companies from high-carbon sectors listed on the Indonesia Stock Exchange (2021–2023). Results indicate carbon emissions do not have a significant impact on earnings quality overall. In regions with high ethical standards, higher carbon emissions reduce earnings quality due to greater earnings management and the rebound effect. In low-ethics regions, higher carbon emissions are linked to better earnings quality, likely from real business growth. Board gender diversity does not significantly moderate this relationship. The study recommends policymakers for improving financial reporting quality and advancing environmental responsibility by considering the ethical and social context of each region.